Autophagy and inflammation in ischemic stroke - Mo, Yun (Neural Regen Res, 2020)
Appropriate autophagy has protective effects on ischemic nerve tissue, while excessive autophagy may cause cell death. The inflammatory response plays an important role in the survival of nerve cells and the recovery of neural tissue after ischemia. Many studies have found an interaction between autophagy and inflammation in the pathogenesis of ischemic stroke. This study outlines recent advances regarding the role of autophagy in the post-stroke inflammatory response as follows. (1) Autophagy inhibits inflammatory responses caused by ischemic stimulation through mTOR, the AMPK pathway, and inhibition of inflammasome activation. (2) Activation of inflammation triggers the formation of autophagosomes, and the upregulation of autophagy levels is marked by a significant increase in the autophagy-forming markers LC3-II and Beclin-1. Lipopolysaccharide stimulates microglia and inhibits ULK1 activity by direct phosphorylation of p38 MAPK, reducing the flux and autophagy level, thereby inducing inflammatory activity. (3) By blocking the activation of autophagy, the activation of inflammasomes can alleviate cerebral ischemic injury. Autophagy can also regulate the phenotypic alternation of microglia through the nuclear factor-κB pathway, which is beneficial to the recovery of neural tissue after ischemia. Studies have shown that some drugs such as resveratrol can exert neuroprotective effects by regulating the autophagy-inflammatory pathway. These studies suggest that the autophagy-inflammatory pathway may provide a new direction for the treatment of ischemic stroke.